2010
DOI: 10.4103/0975-5950.69150
|View full text |Cite
|
Sign up to set email alerts
|

Unusual causes of reduced mouth opening and it′s suitable surgical management: Our experience

Abstract: Reduced mouth opening is a common clinical problem and many individuals experience it at least once in his or her life and most dental practitioners see patients with restricted mouth opening quite often. It can occur due to a variety of underlying conditions which may involve complex factors. Hence, it is essential for the clinician to thoroughly investigate and examine these cases for proper diagnosis and its appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…From our results, the flap width was between 5 and 9 cm with a mean width of (30). The average mouth opening in this study was 36.18±10.12 mm which is similar to the results of a study of Weber et al, 2010 (31) and higher than that found by another study by Scott et al, 2008 (32) where the average mouth opening was 32 mm.…”
Section: Discussionsupporting
confidence: 90%
“…From our results, the flap width was between 5 and 9 cm with a mean width of (30). The average mouth opening in this study was 36.18±10.12 mm which is similar to the results of a study of Weber et al, 2010 (31) and higher than that found by another study by Scott et al, 2008 (32) where the average mouth opening was 32 mm.…”
Section: Discussionsupporting
confidence: 90%
“…Oral submucosal fibrosis (OSMF) is a chronic and complex debilitating disease of the oral cavity, that extends to the oropharynx, progressively increasing fibrosis, epithelial dysplasia [1] and higher incidence of leukoplakia [1,2]. In the later stages of the disease, trismus (limited mouth opening) and severe scarring are the norm [3]. While OSMF was earlier confined to Indian subcontinent and nearly 5 million cases have been reported [4][5][6], it has now spread to Asian population of the UK, the USA and other developed countries and is a global health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Limited mouth opening makes reaching posterior regions difficult or impossible. Restricted mouth opening can occur due to a variety of underlying conditions which may involve complex medical and psychological factors (26). Trismus is defined as an inability to open the mouth due to masticator muscle spasm or fibrosis (27).…”
Section: Limited Accessmentioning
confidence: 99%